Ecological security pattern for the landscape of mesoscale and microscale land: a case study of the Harbin city center - Yuanjing, Zhang; Binyang, Yu; Ashraf, Muhammad Aqeel (Journal of Environmental Engineering and Landscape Management, 2015)
The city center planning based on the ecological security pattern of the landscape plays an important role in protecting the healthy operation of the urban ecological environment. This paper takes the city of Harbin of Heilongjiang Province as the target of research, the data during 2011 and 2012 relating to the overall urban planning of Harbin as the data source, and the extraction of the study domain based on the principle of landscape ecology as the ecological source. Also, we take the cumulative cost distance model to create the ecological corridor and the ecological nodes, build the spatial pattern of the city center based on the ecological security pattern of the landscape, and develop the strategy to protect the ecological security pattern of the city center landscape. This study has a pivotal reference value for guiding the city’s overall planning and protecting the ecological environment of the region.